Editor's Introduction to the Kenya Edition, Nairobi: Vita Books 2021. (28th August 2022) - Oyoo, Sungu
Abstract : Written 25 years ago, Kenya: A Prison Notebook has inspired generations and proved a great resource and a hand book in political education in Kenya and beyond. It chronicles Maina Wa Kinyatti's arrest and detention by the Moi regime, and powerfully captures Kenya's history.